Diagnostic challenge and biopsychosocial approach in burning mouth syndrome management - Ni Putu Yessy Karmila Putri; Anandina Irmagita Soegyanto; Indriasti Indah Wardhany; Ambar Kusuma Astuti; Ratna Kumala Indrastiti (Majalah Kedokteran Gigi Indonesia, 2026)
Burning mouth syndrome (BMS) is a chronic pain disease marked by a prolonged burning sensation in clinically healthy oral mucosa, commonly occurs in fifth to seventh decade women with hormonal changes or psychological problems. Establishing a diagnosis that excludes any apparent organic cause for BMS complaints can be challenging. This case study aimed to determine how the diagnosis and biopsychosocial approach were made in the management of BMS patients. A 53-year-old female patient presented to the Oral Medicine Clinic, Dental Hospital, Faculty of Dentistry, Universitas Indonesia, with a two-month history of burning sensation throughout the oral mucosa and radiating pain affecting the tongue and gums. Last menstrual cycle was three years ago. She admitted to feeling stress and anxiety over her mouth condition and family problems. Extraoral examination revealed dry lips, and intraoral examination showed normal oral mucosa and multiple missing teeth. The Depression Anxiety Stress Scale (DASS-21) showed moderate anxiety and stress levels. The patient was diagnosed with burning mouth syndrome. Reassurance was given on the first visit to help reduce anxiety caused by chronic pain, along with the use of prescribed combination of neurotropic vitamins containing analgesic and stress management. After six weeks, the pain and burning sensation subsided. In order to effectively manage BMS in patients with psychological conditions, a thorough evaluation and comprehensive therapy are important. A successful combination of psychological and medical strategies will be greatly beneficial in the treatment of BMS patients.